Complete Genome Sequence Analysis of Enterobacter sp. SA187, a Plant Multi-Stress Tolerance Promoting Endophytic Bacterium - Andrés-Barrao, Cristina; Lafi, Feras F.; Alam, Intikhab; de Zélicourt, Axel; Eida, Abdul A.; Bokhari, Ameerah; Alzubaidy, Hanin; Bajic, Vladimir B.; Hirt, Heribert; Saad, Maged M. (Frontiers in Microbiology, 2017)
Enterobacter sp. SA187 is an endophytic bacterium that has been isolated from root nodules of the indigenous desert plant Indigofera argenta. SA187 could survive in the rhizosphere as well as in association with different plant species, and was able to provide abiotic stress tolerance to Arabidopsis thaliana. The genome sequence of SA187 was obtained by using Pacific BioScience (PacBio) single-molecule sequencing technology, with average coverage of 275X. The genome of SA187 consists of one single 4,429,597 bp chromosome, with an average 56% GC content and 4,347 predicted protein coding sequences (CDS), 153 ncRNA, 7 rRNA and 84 tRNA. Functional analysis of the SA187 genome revealed a large number of genes involved in uptake and exchange of nutrients, chemotaxis, mobilization and plant colonization. A high number of genes were also found to be involved in survival, defense against oxidative stress and production of antimicrobial compounds and toxins. Moreover, different metabolic pathways were identified that potentially contribute to plant growth promotion. The information encoded in the genome of SA187 reveals the characteristics of a dualistic lifestyle of a bacterium that can adapt to different environments and promote the growth of plants. This information provides a better understanding of the mechanisms involved in plant-microbe interaction and could be further exploited to develop SA187 as a biological agent to improve agricultural practices in marginal and arid lands.